ANALISIS SEKTOR POTENSIAL DI KABUPATEN KARANGASEM PROVINSI BALI - I Kadek Santa, Ambara; I Nyoman, Mahendra Yasa (PIRAMIDA, 2019)
Regional development as an integral of national development is a process of planned change achieve the goals and objectives to improve the welfare of the community that involves all existing activities. Kabupaten Karangasem has an economic growth that tends to decrease from year to year, so this research is done in Krangasem District. The purpose of this study is to analyze which sectors are the basis sector in karangasem district, to analyze the most important sector in karangasem district, to analyze which sector become potential sector in Karangasem regency with DLQ analysis technique. Result of research indicate that sector which become base sector in Regency of Karangsem there are 6 sector, dominant sector in Regency of Karangasem there are 13 sector, and potential sector which become development priority in Regency of Karangasem there are 7 sector.